PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE KOOPERATIF TIPE GROUP INVESTIGATION MATA PELAJARAN PKN KELAS V SD 165730 KOTA TEBING TINGGI - Onomdina Onomdina (PGSD Universitas Negeri Medan, 2018)
This purposes of this research is to improve learning result on PKn subject through cooperative method group investigation type. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class V, SD N 165730 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the cooperative method group investigation typeof PKn subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (66,67%), the first cycle (72,72%), cycle II (90,90 %) and complete learn the clasical equal to 90,90 %.Keywords :Cooperative, Group Investigation, Learning Result